Analisis Dan Desain Sistim Informasi Perpustakaan Migrasi Ke Digital Library - N. Suruali; D. B. Paillin (ARIKA, 2010)
Library has some aims in order to increase the management and services of library. One of the aim is that providing some information source and utilizing information technology. Library, which has its own information system, will be more easier in managing and library servicing. The methodology is done in three steps. At the preparing step was collecting the data through literature study and benchmarking of some typical library. In the analysis step was analyzed one for an existing system and also the new library system to be built. The analysis was including the organization preparedness using the library job description, analysis for digital library development principal using ten development principal of digital library, analysis for three main library activities which is directly connected to the system, analysis for database system using data integrated approach with database management system (DBMS), and analysis for an actors. The design for digital library system was used unified modelling language (UML). The test of Analysis and Design system was used CRC Model. The digital library to be designed in more ideal for facing the demography and the needs. Another aspect to be consider in converting the source in the digital form is the copyright and the network security system.